Facial Personal Protective Equipment: Materials, Resterilization Methods, and Management of Occupation-Related Dermatoses. Issue 2 (March 2021) - Yu, JiaDe; Goldminz, Ari; Chisolm, Sarah; Jacob, Sharon E.; Zippin, Jonathan H.; Wu, Peggy A.; Hylwa, Sara; Dunnick, Cory A.; Chen, Jennifer K.; Reeder, Margo; Honari, Golara; Atwater, Amber Reck
Abstract : Background: The coronavirus infectious disease 2019 pandemic has resulted in health care workers donning personal protective equipment (PPE) for extended periods. Objectives: The aims of the study were to review facial PPE (surgical masks and N95 respirators) ingredients, to identify facial PPE resterilization techniques, and to recommend strategies for prevention and management of facial PPE–related dermatoses. Methods: Twenty-one facial PPE (11 N95 respirators, 10 surgical masks) were reviewed. Resterilization techniques were identified. Personal protective equipment–induced occupational dermatoses and management strategies were explored. Results: Polypropylene is the most common chemical identified in facial PPE. Most masks contain aluminum at the nosepiece. Two surgical masks released nickel. Facial PPE dermatoses include irritant contact dermatitis, allergic contact dermatitis, acne, and contact urticaria. Strategies for prevention and management of facial PPE occupational dermatoses are discussed. Conclusions: There are increasing reports of occupational dermatoses associated with facial PPE. This review discusses the components of facial PPE, mask resterilization methods, and strategies for prevention and management of facial PPE dermatoses.